Application of The Eoq Model to Web-Based Inventory Control Application In Companies - Yurindra, Y; Wijaya, Benny (IJISTECH (International Journal of Information System and Technology), 2025)
Inventory of goods is one of the important components in a company. Problems occur in the management of companies that still use a manual system, so that companies have difficulty determining the stock of updated goods, recaping incoming and outgoing goods, and making routine reports. This will affect the next inventory planning and the company makes inventory with estimated needs or when goods run out without being known. To overcome this problem, an application is needed that can manage the company's inventory of goods. This study uses object-oriented methods and prototyping models. Accompanied by an inventory planning calculation model using the Economic Order Quantity model. In its design, it uses a unified modelling language, encoded with the PHP programming language, and tests are carried out with black-box testing. Inventory control applications built on the web by implementing Economic Order Quantity as inventory planning can run well, so that companies can use them to overcome inventory management and planning problems.